2018
DOI: 10.3947/ic.2018.50.3.252
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness, Safety, and Tolerability of a Switch to Dual Therapy with Dolutegravir Plus Cobicistat-Boosted Darunavir in Treatment-Experienced Patients with Human Immunodeficiency Virus

Abstract: BackgroundDual regimen with dolutegravir plus cobicistat-boosted darunavir (DTG/DRV/c) is reasonable alternative option for patients with existing resistance and/or intolerance to nucleoside reverse transcriptase inhibitors (NRTIs).Material and MethodsAll patients who switched to DTG/DRV/c among treatment-experienced patients with human immunodeficiency virus (HIV) in a tertiary university hospital were selected. We analyzed the effectiveness, safety, and tolerability based on serial laboratory data and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Finally, PI drugs could also constitute an efficient option for these children and adolescents, as most of these ARV drugs, especially darunavir, remained fully efficient (15/15; 100%). Indeed, the use of dolutegravir in combination with darunavir in cART-experienced HIV-infected patients has been demonstrated to be convenient in switch therapy 55 , 56 . However, the cobicistat-boosted darunavir (darunavir/c) formulation should be preferred to ritonavir-boosted darunavir (darunavir/r), as darunavir/r reduces the plasma concentrations of dolutegravir when prescribed in combination, 57 unlike darunavir/c, which has very minimal impact on dolutegravir plasma concentrations 58 …”
Section: Discussionmentioning
confidence: 99%
“…Finally, PI drugs could also constitute an efficient option for these children and adolescents, as most of these ARV drugs, especially darunavir, remained fully efficient (15/15; 100%). Indeed, the use of dolutegravir in combination with darunavir in cART-experienced HIV-infected patients has been demonstrated to be convenient in switch therapy 55 , 56 . However, the cobicistat-boosted darunavir (darunavir/c) formulation should be preferred to ritonavir-boosted darunavir (darunavir/r), as darunavir/r reduces the plasma concentrations of dolutegravir when prescribed in combination, 57 unlike darunavir/c, which has very minimal impact on dolutegravir plasma concentrations 58 …”
Section: Discussionmentioning
confidence: 99%
“…No participant developed new drug resistance mutations throughout the study [49]. Additional observational studies have demonstrated similar results although DRV/r and/or DTG was allowed twice daily [48] while another retrospective study demonstrated the feasibility of cobicistat-boosted DRV with DTG once daily in treatment-experienced patients [50].…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, a study of 31 treatment-experienced individuals in Korea demonstrated high success rates with a switch to cobicistat-boosted darunavir with dolutegravir. Of 18 individuals who were baseline suppressed, 100% maintained viral suppression and of 13 individuals who were baseline non-suppressed, 11 reached viral suppression [18]. A smaller study evaluated a switch from complex salvage regimens to ritonavir-boosted darunavir with dolutegravir among 13 individuals with transmitted NRTI resistance and found that all 13 individuals tolerated the regimen with continued viral suppression after 12 months [19].…”
Section: Discussionmentioning
confidence: 99%
“…Median duration since HIV diagnosis was 22 years (IQR 16-28). Median duration of prior ART use was 19 years (IQR [13][14][15][16][17][18][19][20][21][22]. Of the 65 individuals, 100% had prior exposure to nucleoside(tide) reverse transcriptase inhibitors (NRTI), 85% to non-nucleoside reverse transcriptase inhibitors (NNRTI), 89% to protease inhibitors (PI) and 57% to integrase strand transfer inhibitors (INSTI).…”
Section: Description Of Cohort On Boosted Darunavir With Dolutegravir (Study Regimen)mentioning
confidence: 99%